One Verse, Two Settings, and Three Strange Youths - Rizzuti, Alberto (Gli spazi della musica, 2013)
Bach’s Latin Magnificat is the core of a constellation of works textually, liturgically, and musically interwoven. One year after composing the original version in E-flat major (BWV 243a, for the Feast of Visitation of 1723), Bach composed Meine Seele erhebt den Herren (BWV 10), a cantata whose text is in part a translation and in part a paraphrase of the Canticum Mariae. Exploring the setting of the Latin text and that of its German translation/paraphrase, this paper aims at shedding light on the musical and – broadly speaking – cultural relationship between the two works. Un verso, due intonazioni e tre strani giovani Il Magnificat latino di Bach è al centro di una costellazione di lavori variamente collegati in termini testuali, liturgici e musicali. Un anno esatto dopo aver composto la versione originale in mi bemolle maggiore (BWV 243a, per la Festa della Visitazione del 1723), Bach compose Meine Seele erhebt den Herren (BWV 10), una cantata il cui testo verbale è in parte una traduzione e in parte una parafrasi del Canticum Mariae. Indagando la messa in musica del testo latino del cantico e quello tedesco della sua traduzione/parafrasi, questo saggio tenta di far luce su un passo in cui i due lavori intrattengono un originale rapporto testuale e lato sensuculturale.